2007
DOI: 10.1051/0004-6361:20078072
|View full text |Cite
|
Sign up to set email alerts
|

Clathrate hydrates as a sink of noble gases in Titan's atmosphere

Abstract: We use a statistical thermodynamic approach to determine the composition of clathrate hydrates which may form from a multiple compound gas whose composition is similar to that of Titan's atmosphere. Assuming that noble gases are initially present in this gas phase, we calculate the ratios of xenon, krypton and argon to species trapped in clathrate hydrates. We find that these ratios calculated for xenon and krypton are several orders of magnitude higher than in the coexisting gas at temperature and pressure co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 15 publications
0
49
1
Order By: Relevance
“…61 The Kr and Xe deficiencies could simply be explained by the presence of clathrates on the surface of Titan that would have efficiently incorporated these noble gases. 7,52 On the other hand, in order to interpret the Ar deficiency in the atmosphere of Titan, it has been proposed that the satellite was formed from icy planetesimals initially produced in the solar nebula and that were partially devolatilized at a temperature not exceeding ∼ 50 K during their migration within Saturn's subnebula. 13 In this case, because Ar is poorly trapped in clathrates formed above ∼ 50 K in the nebula, only tiny amounts of this compound would have been incorporated in the building blocks of the forming Titan, in agreement with the observations.…”
Section: The Argon Deficiency In Titanmentioning
confidence: 99%
See 1 more Smart Citation
“…61 The Kr and Xe deficiencies could simply be explained by the presence of clathrates on the surface of Titan that would have efficiently incorporated these noble gases. 7,52 On the other hand, in order to interpret the Ar deficiency in the atmosphere of Titan, it has been proposed that the satellite was formed from icy planetesimals initially produced in the solar nebula and that were partially devolatilized at a temperature not exceeding ∼ 50 K during their migration within Saturn's subnebula. 13 In this case, because Ar is poorly trapped in clathrates formed above ∼ 50 K in the nebula, only tiny amounts of this compound would have been incorporated in the building blocks of the forming Titan, in agreement with the observations.…”
Section: The Argon Deficiency In Titanmentioning
confidence: 99%
“…[4][5][6][7][8] Moreover, it has been suggested that the activity observed in some cometary nuclei results from the dissociation of these crystalline structures. 9 Generally speaking, clathrates probably participated in the formation of planetesimals in the solar system.…”
Section: Introductionmentioning
confidence: 99%
“…Thomas et al (2007) have proposed the formation of clathrate hydrates on Titan's surface as a sink for krypton and xenon, while Osegovic & Max (2005) have calculated that compound clathrates could explain the absence of xenon and presumably krypton as well. The arguments presented above show that the special conditions required for clathrate formation are not required to explain the T. Owen and H. B. Niemann upper limits on these two gases given the detection threshold of the GCMS.…”
Section: (D ) Noble Gasesmentioning
confidence: 99%
“…The authors calculated the composition of clathrates on the surface of Titan using the program CSMHYD (developed by Sloan (1998)) and showed that such crystalline ice structures may act as a sink for Xe. The facts that the code used by Osegovic & Max (2005) is not suitable below about 140 K for gas mixtures of interest, and that the authors did not explicitly calculate the trapping efficiencies of Ar and Kr in clathrates on the surface of Titan led Thomas et al (2007) to reconsider their results. In particular, Thomas et al (2007) performed more accurate calculations of the trapping of noble gases in clathrates using a statistical thermodynamic model based on experimental data and on the original work of van der Waals & Platteeuw (1959).…”
Section: Introductionmentioning
confidence: 99%
“…The facts that the code used by Osegovic & Max (2005) is not suitable below about 140 K for gas mixtures of interest, and that the authors did not explicitly calculate the trapping efficiencies of Ar and Kr in clathrates on the surface of Titan led Thomas et al (2007) to reconsider their results. In particular, Thomas et al (2007) performed more accurate calculations of the trapping of noble gases in clathrates using a statistical thermodynamic model based on experimental data and on the original work of van der Waals & Platteeuw (1959). On this basis, Thomas et al (2007) showed that Xe and Kr could have been progressively absorbed in clathrates located at the surface of Titan during its thermal history, in contrast with Ar, which is poorly trapped in these crystalline structures.…”
Section: Introductionmentioning
confidence: 99%